B lymphocytes: development, tolerance, and their role in autoimmunity-focus on systemic lupus erythematosus. (2013)
B lymphocytes are the effectors of humoral immunity, providing defense against pathogens through different functions including antibody production. B cells constitute approximately 15% of peripheral blood leukocytes and arise from hemopoietic stem cells in the bone marrow. It is here that their antigen receptors (surface immunoglobulin) are assembled. In the context of autoimmune diseases defined by B and/or T cell autoreactive that upon activation lead to chronic tissue inflammation and often irreversible structural and functional damage, B lymphocytes play an essential role by not only producing autoantibodies but also functioning as antigen-presenting cells (APC) and as a source of cytokines. In this paper, we describe B lymphocyte functions in autoimmunity and autoimmune diseases with a special focus on their abnormalities in systemic lupus erythematosus.